JENIS-JENIS SERANGGA YANG BERASOSIASI PADA ECENG GONDOK DI DANAU TONDANO - Geyby ., Kumolontang; Max ., Tulung; Christina L. Salaki (AGRI-SOSIOEKONOMI, 2017)
This study aims to see the abundance of species and populations of insects found in water hyacinth vegetation in Tondano Lake. Â This research was conducted at Entomology and Phytopathology Laboratory of Agriculture Faculty at Sam Ratulangi University in Manado and on the coast of Tondano Lake. This study was conducted for 3 months. The research method used purposive sampling method or intentional intake at 5 point location of hyacinth vegetation in Tondano Lake. Determination of Research Location is based on the amount of area that has been covered by water hyacinth on the coast of Tondano. On each location has been determined and then made a plot of sampling area of 10 x 10 m. The results showed that the types of insects found in the hyacinth vegetation in Tondano Lake were from family: Culicidae, Muscidae, Phoridae, Sepsidae, Drosopilidae, Apdididae, Anthomyidae, Carabidae, Dolichopodidae, Braconidae, Stratiomiidae, Ichneumonidae, Cecidomidae, Bombylidae and Sphingidae. Insect populations fluctuate in each observation. The existence of insects found in hyacinth vegetation in Tondano Lake is generally caused by the close distance between water hyacinth with rice fields and plantations and the existence of decaying vegetation that can be a good habitat for these breeding insects, in addition there are also enemies naturally found due to its activities in the search for prey.Â